Wakefield excitation in plasma-dielectric structures by a sequence relativistic electron bunches - Kiselev, V.A.; Linnik, A.F.; Onishchenko, I.N.; Pristupa, V.I.; Sotnikov, G.V.; Berezina, G.P. (Вопросы атомной науки и техники, 2015)
he results of theoretical and experimental studies of the influence of the plasma in the transit channel of dielectric structure on the efficiency of wakefield excitation by a sequence of relativistic electron bunches are presented. The dielectric structure of circular cross-section with Teflon (ε=2.1; tgδ=2·10⁻⁴) The plasma in the channel dielectric structure is formed by passing bunches of relativistic electrons through the neutral gas as a result of impact ionization and acceleration of plasma electrons in the excited wake wave. It is shown that when the gas pressure in the range 10⁻²…1 Torr, an increase of the amplitude of the excited wakefield due to changes in the topography of the main electromagnetic mode. In the pressure range 0.1…1 Torr observed focusing electron bunches due to the presence of bunches in the decelerating the total longitudinal electromagnetic field and Langmuir wave and at the same time focusing field of the Langmuir wave.